The Isra'iliyyat (of the Israelites) of the Story of Mary and Jesus (p.b.u.t) in Shia and Sunny Commentaries, with Emphasis on Behar al- Anwar (Seas of Lights) - faeze Sadat khosravi; سیده وحیده رحیمی (پژوهش‌های تفسیر تطبیقی, 2015)
The present research entitled "the Isra'iliyyat of the story of Mary and Jesus (p.b.u.t) in Shia and Sunny commentaries, with emphasis on Behar al-Anwar" was conducted with the aim of extracting the Isra'iliyyat of Behar al-Anwar in narrating the stories of Mary and Jesus. It is mainly aimed at extracting the Isra'iliyyat of these stories and elaborating on how Allamah Majlesi  addressed these narratives and their narrators by studying the text of the Behar al-Anwar, reviewing  Allamah's other works and comparing and contrasting them with Shia and Sunny commentaries. Some scholars, including Allamah Tabatabaii and Allamah Askari, believe that Majlesi had not tried to select valid narratives and differentiate them from weak ones and had only gathered all valid and invalid hadiths in Behar al-Anwar without considering their validity or invalidity in relation to infallible Imams, while the analysis of his "remarks" and  explanations under the aforementioned narratives and comparing them with other commentaries show that general public's conception contradicts with how Majlesi had really addressed these narratives. In other words, it should be said that only few Isra'iliyyat can be found among many related narratives, which are explicitly rejected by Majlesi or can be invalidated on the basis of Majlesi's other criteria for other narratives, because there are many instances of his explicit and clear rejection of Isra'iliyyat and their narrators in all parts of Behar al-Anwar. Therefore, it should be said that Allamah Majlesi had carefully selected the narrations on the basis of his specific criteria and had thus prevented the entrance of many Isra'iliyyat into Behar al-Anwar as a complete collection of hadiths. So, it can be concluded that attention to Isra'iliyyat, their narrators and explicit and clear rejection of such narratives is one of the Majlesi's important criteria for selecting narratives for Behar al-Anwar. Seyyedeh Vahideh Rahimi[1]